Pengelolaan Hipertensi Sebelum Kehamilan - Adela Putri Agata (Penerbit Goodwood, 2022)
Purpose : this study was to determine the best management in women with a history of hypertension as a form of preparation before pregnancy. Methodology : is a literature review with inclusion criteria of national and international scientific journals for the last ten years (2012-2022) which can be accessed through a search for literature sources by Google Scholar and NCBI Pubmed. Result : there are several recommendations that need to be considered in women with hypertension who planning to become pregnant, which are the use of antihypertensive drugs, blood pressure control, evaluation of the mother's condition before pregnancy, supplementation and lifestyle. Therefore, the need for preparation before pregnancy is important to get a better outcome in women with a history of hypertension. Limitation : This article is only a review of several other articles, not doing research directly. Contribution : With proper examination, it is hoped that women with a history of hypertension can have a better outcome when they come to pregnancy.